Liver‐type fatty acid‐binding protein and neutrophil gelatinase‐associated lipocalin in cats with chronic kidney disease and hyperthyroidism. (15th March 2021) - Kongtasai, Thirawut; Meyer, Evelyne; Paepe, Dominique; Marynissen, Sofie; Smets, Pascale; Mortier, Femke; Demeyere, Kristel; Vandermeulen, Eva; Stock, Emmelie; Buresova, Eva; Defauw, Pieter; Duchateau, Luc; et al.
Abstract: Background: Liver‐type fatty acid‐binding protein (L‐FABP) and neutrophil gelatinase‐associated lipocalin (NGAL) are candidate biomarkers for the detection of early chronic kidney disease (CKD) in cats. Objective: To evaluate urinary and serum L‐FABP and NGAL concentrations in CKD cats and in hyperthyroid cats before and after radioiodine ( 131 I) treatment. Animals: Nine CKD cats, 45 healthy cats and hyperthyroid cats at 3 time points including before (T0, n = 49), 1 month (T1, n = 49), and 11 to 29 months after (T2, n = 26) 131 I treatment. Methods: Cross‐sectional and longitudinal study. Serum L‐FABP (sL‐FABP), serum NGAL (sNGAL), urinary L‐FABP (uL‐FABP), and urinary NGAL (uNGAL) were compared between the 3 groups and between hyperthyroid cats before and after treatment. Data are reported as median (min‐max). Results: CKD cats had significantly higher sL‐FABP (13.50 [3.40‐75.60] ng/ml) and uL‐FABP/Cr (4.90 [0.97‐2139.44] µg/g) than healthy cats (4.25 [1.34‐23.25] ng/ml; P = .01 and 0.46 [0.18‐9.13] µg/g; P < .001, respectively). Hyperthyroid cats at T0 had significantly higher uL‐FABP/Cr (0.94 [0.15‐896.00] µg/g) than healthy cats (P < .001), thereafter uL‐FABP/Cr significantly decreased at T2 (0.54 [0.10‐76.41] µg/g, P = .002). For the detection of CKD, uL‐FABP/Cr had 100% (95% confidence interval [CI], 66.4‐100.0) sensitivity and 93.2% (95% CI, 81.3‐98.6) specificity. There were no significant differences in sNGAL and uNGAL/Cr between the 3 groups. Conclusions and Clinical Importance: L‐FABP, but not NGAL, is a potential biomarker for the detection of early CKD in cats. Utility of uL‐FABP to predict azotemia after treatment in hyperthyroid cats remains unknown.